Enhancing Multiplication Memorization in Elementary School: A Cooperative Learning Approach with Kalino Cards - Marlian Marlian; Ester Julinda Simarmata; Rosdiana Samosir (Journal on Education, 2024)
This research analyzes the usefulness of cooperative learning, specifically deploying kalino cards, in boosting multiplication memorization skills among third-grade pupils in an elementary school context. The study employs an iterative strategy, implementing two cycles of intervention with continual refinement based on reflective observations and feedback. Traditional teaching techniques, characterized by lectures and restricted interactive media, exhibited inadequacies in supporting successful multiplication memorization, as evidenced by pre-test results. The inclusion of cooperative learning, integrating kalino cards, resulted in a considerable improvement in post-test scores. The iterative design stressed the necessity of constant reflection, resolving difficulties identified in the first cycle and associating favorably with improved outcomes in the second cycle. Qualitative findings from interviews indicated significant relationships between cooperative learning and increased student involvement and motivation. The usage of score sheets for evaluation also linked positively with student motivation, underscoring the relevance of effective instructional medium. In conclusion, this research demonstrates that cooperative learning with kalino cards holds significant potential for enhancing multiplication memorization skills among elementary school students, contributing valuable insights for educators seeking innovative and collaborative instructional methods.